BIOPOLITICS AND THE BODY IN NAZI CINEMA - Baroni, Raissa (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2018)
From the logocentric culture to the visual culture, the cinema has gained its emancipation as most powerful and important of arts, especially due to the totalitarian strategies that used it toward an aestheticization of politics to control the masses. The following is an analysis of the effects of the totalitarian Nazi power on the body, conducted by means of the German film Triumph of the will by Leni Riefenstahl. On the one hand, through the concept of microphysics of power and the implications of the techniques of the body will be explained how the bio-power works and circulates; on the other hand, this study shows how the viewing of a film can activate the mirror-neurons in our brain and implicate the mimetic desire and the social mimetism.